Legal effort in the case of binomo trading fraud under the disguise of investment and the criminal acts of money laundering are committed in connection with law no. 19 of 2016 and law no. 8 of 2010 - Yenrizka Gusmaria; Tri Setiady (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Trading is very popular in various countries, one of which is Indonesia, this is an activity of buying and selling assets in the financial market with the aim of making a profit. Assets that are usually traded in trading can be stocks, foreign exchange, bonds, gold, cryptocurrencies and other investment instruments. Treaders usually make transactions by buying assets when the price is relatively cheap and selling them again when the price goes up, in the hope of making a profit from the fluctuations in the price of the asset. Some time ago, Indonesia was shocked by a case carried out by one of the influencers, Indra Kesuma alias Indra Kenz, who committed trading fraud in the name of investment through electronic media. From this case, many victims reported because they felt disadvantaged by the suspect, the losses incurred were also very large. In addition to the fraud case committed by the suspect, a money laundering crime was also found to hide or disguise the origin of funds obtained from these illegal activities, so that it appeared as if it came from a legitimate source. This study aims to analyze cases of trading fraud under the guise of investment with the motive of spreading false and misleading news that results in consumer losses. In this study, the author uses quantitative data to analyze the fraud system under the guise of investment and money laundering committed in the case of Indra Kenz through the illegal Online Binary Options (Binomo) gambling platform in Indonesia in relation to Law No. 19 of 2016 concerning Information and Electronic Transactions and Law No. 8 of 2010 concerning Prevention and Eradication of Money Laundering.